1995
DOI: 10.2337/diacare.18.8.1140
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Diabetic Retinopathy and Nephropathy in Polynesians of Western Samoa

Abstract: Diabetic retinopathy and albuminuria are common in Polynesian Western Samoans. Duration of diabetes and level of glycemia were the most important associated factors. These data underline the need for cost-effective programs for the detection and early treatment of diabetes in Western Samoa and other developing populations with high susceptibility to NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 25 publications
3
24
3
Order By: Relevance
“…This is possible because early changes in NPDR are caused by capillary dilatation and leakage, which are associated with the status of hyperglycemia, glycemic control, and comorbidity status factors such as hypertension. 6,23,24 Consistent with previous studies, [7][8][9][10][11][12][13] our results show that the duration of diabetes is strongly associated with NPDR. This suggests that the duration of diabetes is an indicator for the deterioration of type 2 diabetes.…”
Section: Factors Associated With Nonproliferative Diabetic Retinopathysupporting
confidence: 95%
See 2 more Smart Citations
“…This is possible because early changes in NPDR are caused by capillary dilatation and leakage, which are associated with the status of hyperglycemia, glycemic control, and comorbidity status factors such as hypertension. 6,23,24 Consistent with previous studies, [7][8][9][10][11][12][13] our results show that the duration of diabetes is strongly associated with NPDR. This suggests that the duration of diabetes is an indicator for the deterioration of type 2 diabetes.…”
Section: Factors Associated With Nonproliferative Diabetic Retinopathysupporting
confidence: 95%
“…32 Table 5 presents the prevalence of DR in various types of diabetic populations. 7,8,10,[33][34][35][36][37][38][39][40][41][42] In addition to differences in the diagnostic criteria, this disparity is largely due to the different sources of type 2 diabetes. Since subjects with DR in our study were identified among presymptomatic type 2 diabetic patients, a substantial proportion of patients had NPDR, and only a small proportion of diabetic patients had severe DR.…”
Section: Prevalence Of Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the prevalence or incidence of diabetic retinopathy is different among various ethnic groups (7)(8)(9). Chen et al (10) reported that the rate of progression to proliferative diabetic retinopathy (PDR) is higher in Taiwan Chinese than that in Caucasians.…”
mentioning
confidence: 98%
“…In the present study, the incidence and progression of diabetic retinopathy were examined to learn whether Hispanics had excess risk compared with NHWs with type 2 diabetes living in the San Luis Valley of Colorado. Because glucose control, hypertension, type of therapy, and diabetes duration, among other risk factors, are associated with diabetic retinopathy (1,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), we also examined these and other factors to see if they accounted for altered Hispanic-to-NHW incidence rates.…”
mentioning
confidence: 99%